Aspects and approaches for the development of digital training assistants - Lippmann, K.; Senner, V.; Baldinger, M. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
The MotiTrain project aimed to develop an interactive fitness coach and a digital training process companion that can significantly increase the user`s motivation and success in fitness training through innovative approaches and technologies. The system combines gamification approaches, data collection/analysis, and individualized visual and haptic feedback. It detects deviations from the ideal training movement, corrects them in a targeted manner and thus increases the efficiency of the training. It provides users with a virtual personal trainer who accompanies them and supports them via a smartphone or tablet with reminders, exercise suggestions, and an overview of training progress.